SISTEM INFORMASI KEPEGAWAIAN BERBASIS WEB (Studi Kasus: Sekolah Tinggi Teknologi Ronggolawe Cepu) - Azizah Fajr; Joko Handoyo (SIMETRIS, 2015)
Employees is an important subject in an organization. In the absence of a good employee, your organization will be difficult todevelop because of the strength of any organization lies in its employees who manage and handle it. In fixing the system regulating themanagement of staffing at the high school of Technology Cepu Ronggolawe needed a fast, precise and accurate. To avoid ineffectiveness, thedeficiency, and to improve performance in serving the prospective employees, then the required development of the system by changing intoa web-based information systems.Using the approach through several stages for analyzing and designing the system, the process is developed through the use of thecycle of activities and users specifically Analyzer (structured), that is the method of SDLC (System Development Life Cycle) and the waterfallmodel consists of the planning phase of the system, analysis, design, coding, testing, and maintenance. Testing instruments done through testfunctionality and black box testing. In this system for the creation of web-based programs online using Laravel programming language andMySQL by using the Sublime Text 2.Staffing information system is expected to ease the staffing section in the Cepu STTR Staffing process data. The end result of testfunctionality of information systems personnel declared worthy in terms of functionality, with 100% results on black box testing to testing ofsuitability characteristics and accurancy.